Testing Networked ECUs in a HIL Based Integration Lab - Schulte, Thomas; Adenmark, Mikael; Deter, Matthias (SAE 2006 Commercial Vehicle Engineering Congress & Exhibition, October 2006, Rosemont, IL, USA, Session: Systems Engineering Part 1 of 2)
Modern vehicles use Electronic Control Units (ECU), connected via Controller Area Network (CAN) to perform functions. Many of these functions are distributed across several ECUs. This network interconnection enables the sharing of sensors, calculated information and actuators. As new functionality is added, the number of ECUs and their complexity increase.